Diversity of Ground-Dwelling Insects in Varoius Habitat Types of Lembah Sabil, Aceh Barat Daya - Umami, Sharah; Sarong*, Muhammad Ali; Sayuthi, Muhammad; Safrida, Safrida; Djufri, Djufri; Hazmi, Izfa Riza; Emil, Muhammad Farhan Putra (Jurnal IPA & Pembelajaran IPA, 2025)
Ground-dwelling insects play an important role in the decomposition of soil organic matter and serve as bioindicators of environmental degradation, which is reflected by the decline in insect diversity. This study aimed to determine the similarity and diversity levels of ground-dwelling insects and to produce an identification book across different habitat types in Lembah Sabil, Aceh Barat Daya. An exploratory survey method with purposive sampling was applied. The research subjects were all ground-dwelling insects inhabiting various habitats, with observations conducted at four sites in Lembah Sabil. Data were analyzed both quantitatively and qualitatively. The results showed that insect similarity was 59% between coffee plantations and secondary forests, 29% between coastal forests and nutmeg plantations, 36% between coastal forests and coffee plantations, 29% between coastal forests and secondary forests, 42% between coffee and nutmeg plantations, and 48% between nutmeg plantations and secondary forests. Diversity levels were categorized as moderate, with index values of 2.69 in coastal forests, 2.54 in coffee plantations, 2.25 in nutmeg plantations, and 2.43 in secondary forests. The feasibility test of the identification book yielded a score of 76%, indicating it is suitable for use. In conclusion, the similarity of ground-dwelling insects in coastal forests was low, while coffee plantations, nutmeg plantations, and secondary forests exhibited higher similarity. The diversity levels across all four habitat types were classified as moderate